OP0254-HPR Hand exercise for women with rheumatoid arthritis and decreased adl ability: an exploratory randomised controlled trial. (15th June 2017) - Ellegaard, K; von, C Bülow; Røpke, A; Bartholdy, C; Hansen, IS; Rifbjerg, S; Christensen, R; Henriksen, M; Waehrens, E
Abstract : Background: Decreased strength and range of motion in the hand are often seen in rheumatoid arthritis (RA). Positive effects on hand function in RA patients after hand exercise and individual education in joint projection including coping strategies (ADL education) is shown (1;2). However, it is unknown if a combination of both will further improve hand performance. Objectives: To investigate the effect on ADL ability of a hand exercise program as add on to an ADL education program in women with RA. Methods: Women with RA involving the hand on stable medication for at least three months were recruited. At baseline participants were examined by a rheumatologist who assessed joints of the hand and ruled out contraindications for participation e.g. massive malalignment of the joints. Inflammatory markers of the blood, hand pain and grip strength were also measured. The ADL motor ability was assessed using the observation-based Assessment of Motor and Process Skills (AMPS). After baseline examination randomized to ADL education + hand exercises (intervention; IG) or only ADL education (control; CG) was made. All participants received three to four sessions with an occupational therapist learning how to perform ADL tasks overcome their specific hand problems. The intervention group also received a hand exercise program, to be conducted four times a week, for eight weeks, containing exercises for improving range of motion and strength; once a week the exercise program was supervised by a physiotherapist, to correct and prevent overload and to increase load if possible. Primary outcome measure was change in observed ability to perform ADL tasks (AMPS) at week 8. Secondary outcomes include grip strength, pain, joint count, inflammatory markers and self-reported function. After eight weeks, all baseline measures were repeated and changes from baseline were calculated based on the Intention To Treat (ITT) population. Clinicaltrials.gov Identifier: (NCT02140866 ) Results: Fifty five patients were randomised to IG (n=28) or CG (n=27); 22 and 25 patients, respectively, completed the trial. The ITT-populations mean age was 63.8 (12.8) years, mean disease duration was 12.4 (11.0) years. Baseline tender and swollen joint count was 5.07 (4.85) and 1.37 (1.72) respectively, the hand pain was 41.95mm (right) and 35.78mm (left) (VAS) and hand grip strength was 18.25 kg (right) and 17.46 kg (left). Baseline AMPS ADL motor measure was 1.36 (0.46). As judged by the 95% confidence intervals, no difference in change from baseline was seen between the groups (see table). Conclusions: A hand exercise program as add on to an ADL education did not improve ADL ability more than ADL education alone in women with RA experiencing decreased ADL ability involving the hands. References: Masiero S et al. Effects of an educational-behavioral joint protection program on people with moderate to severe rheumatoid arthritis: a randomized controlled trial. Clin Rheumatol 2007 Dec;26:2043–50. Lamb SE et al. Exercises to improve function of the rheumatoid hand (SARAH): a randomised controlled trial. Lancet 2015 Jan 31;385(9966):421–9. Disclosure of Interest: None declared